Pengaruh Strategi Belajar Crossword Puzzle Terhadap Hasil Belajar PAI Siswa Kelas 7 di SMP Negeri 3 Ampek Angkek - Annisa Azmi; Darul Ilmi; Al Baihaqi Anas; Januar Januar (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This research is motivated by low student learning outcomes. In addition, during the learning process the teacher only uses the lecture method in delivering material and there are no variations in strategies or supporting learning media used by the teacher. Therefore learning in class does not involve student activity so that students tend to be less interested in learning. The purpose of this research is to find out how much influence the learning strategy hascrossword puzzle on the results of PAI learning for grade 7 students of SMP Negeri 3 Ampek Angkek. The type of research used islike an experiment with shapenon-equivalent control group design. The sample in this study consisted of 2 classes, namely class 7.1 as the experimental class and class 7.2 as the control class. Data collection in this study uses the resultspre-test andpost-test multiple choice question. The data analysis technique used is the Normality test, Wilcoxon test, Spearman Rank Correlation test, Coefficient of Determination test and Mann Whitney test. The results of calculations from the test of the coefficient of determination, the statistical results obtained are the contribution of learning strategiescrossword puzzle on PAI learning outcomes by 81.9%.